2022
DOI: 10.1242/dev.200356
|View full text |Cite
|
Sign up to set email alerts
|

Normal Table of Xenopus development: a new graphical resource

Abstract: Normal tables of development are essential for studies of embryogenesis, serving as an important resource for model organisms, including the frog Xenopus laevis. Xenopus has long been used to study developmental and cell biology, and is an increasingly important model for human birth defects and disease, genomics, proteomics and toxicology. Scientists utilize Nieuwkoop and Faber's classic ‘Normal Table of Xenopus laevis (Daudin)’ and accompanying illustrations to enable experimental reproducibility and reuse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 89 publications
3
46
0
Order By: Relevance
“…In line with the previous electrophysiological evidence demonstrating that embryos first become polarized at the blastula stage 16 , we found that Barium treatment affected embryonic development primarily when embryos were treated from blastula stages through gastrulation rather than at earlier cleavage stages (Fig. 1b, c, f, g, j-l) 17 . Embryonic development was affected in two ways: (1) 37 ± 3% (SEM) of the embryos failed to complete gastrulation (compared to just 4.7 ± 1% in control embryos) (Fig.…”
Section: M Of the Blastula Regulates Lr Patterning And Gastrulationsupporting
confidence: 91%
“…In line with the previous electrophysiological evidence demonstrating that embryos first become polarized at the blastula stage 16 , we found that Barium treatment affected embryonic development primarily when embryos were treated from blastula stages through gastrulation rather than at earlier cleavage stages (Fig. 1b, c, f, g, j-l) 17 . Embryonic development was affected in two ways: (1) 37 ± 3% (SEM) of the embryos failed to complete gastrulation (compared to just 4.7 ± 1% in control embryos) (Fig.…”
Section: M Of the Blastula Regulates Lr Patterning And Gastrulationsupporting
confidence: 91%
“…This timing is very interesting from a functional point of view. We lack data on the behavior of developing turtles, but in Xenopus laevis, in embryos between stages 32 and 37/38, in which, based on our data, the MP expansion has not yet begun [ (Moreno and González, 2017); present results], simple mechanisms derived from contact reflexes (non-vestibular), mediate the orientation of scape swimming response (Roberts et al, 2000), such this behavioral response begins to be seen at this point in development (Zahn et al, 2022). Therefore, the functional/behavioral capabilities of this model, attributed to the MP (see above), could (i) start to operate at later stages of development, or (ii) it could be the additional territories, already specified at these stages, functionally involved in this task, or (iii) even with the MP at a low degree of development, it could already be involved in these functions.…”
Section: Cytoarchitectonic Organization Of the Medial Palliummentioning
confidence: 78%
“…To resolve this situation, Xenbase commissioned a new set of open-access drawings of Xenopus embryos to generate a new comprehensive suite of reference images not only covering those in the Nieuwkoop and Faber images but also expanding the representation to include additional views and stages missed in the original resource ( Zahn et al 2022 ). These new images complement those generated by Zahn et al ( 2017 ) that initiated this project with a set of drawings focused on stages and orientations relevant to craniofacial development. The new set comprises 133 high-quality illustrations spanning from fertilization to post-metamorphosis, all available under a noncommercial creative commons license and freely usable by the research community.…”
Section: Anatomy Resources and The Zahn Drawingsmentioning
confidence: 82%